LAZISMU Medan’s Communication Strategy to Strengthen Bil Hal Preaching via Zakat, Infaq, Sadaqah - Novia Irawan Dalimunthe; Farhan Indra (Journal of Social Work and Science Education, 2026)
This study aims to analyze the communication strategies of the Muhammadiyah Zakat, Infaq, and Charity Institution (LAZISMU) in Medan City in strengthening da’wah bil hal through zakat, infaq, and charity (ZIS) programs amid the dynamics of a heterogeneous urban society. This study uses a qualitative approach with a case study design. Data collection techniques were carried out through in-depth interviews, participatory observation, and documentation involving administrators, donors, and beneficiaries. Data analysis uses an interactive model that includes data reduction, data presentation, and drawing conclusions, while data validity is maintained through triangulation and member checking techniques. The results of the study indicate that LAZISMU Medan City implements an integrated communication strategy by combining interpersonal communication and digital media. Direct approaches such as visits, socialization, and community involvement have proven effective in building trust and emotional closeness with donors. Meanwhile, the use of digital media such as WhatsApp, Instagram, and Facebook plays an important role in expanding the reach of information, increasing transparency, and encouraging public participation. The implementation of da’wah bil hal through ZIS programs in education, humanitarian social, and economic empowerment fields show a shift from a charitable approach to empowerment, thereby providing tangible social, economic, and spiritual impacts for the beneficiaries.